Os poderes do juiz nos procedimentos civis do estatuto da criança e do adolescente - Mauro, Renata Giovanoni Di (2011)
This thesis aims to recognize the judge powers regarding the flexibility of civil proceedings on the Statute of Children and Adolescents. In this area, the caput of article 153 of Law n. 8.069/90, and its sole paragraph, they become the legal instruments that legitimize such procedural flexibility, in order that the children and adolescents effective overall protection is a reality. It follows that the interpretation methods assume a significant role, because they reveal the real meaning and significance of the words above the legal provisions. The use of hermeneutics shows that the ex officio role in the proceedings of voluntary jurisdiction, supported, including Article 1109 of the Code of Civil Procedure, is a response to the need for simplification of the procedural acts and the adequacy of the procedural sequence requires that each factual situation. On the other hand, as for the acting ex officio to the procedures of contentious jurisdiction, the use of interpretative methods in the study of Article 153 and its sole paragraph, of the Children and Adolescents statute, shows that the relaxation is subject to the approval of the litigants as well as the prosecutor when it is not a party. Protection (constitutional and infraconstitutional) focused on children and adolescents inspires effectiveness in adjudication, justifying the use of procedural flexibility. It is not about permission to arbitrariness, but breaking the excessive formalism, which enables the concentration of process and change as a result of such acts, so that the full protection of the child comes true, no violation of the principles and procedural lien